The immortal life of Henrietta Lacks [videorecording (DVD)] - Wolfe, George C.; Winfrey, Oprah; Byrne, Rose; Goldsberry, Renée Elise, 1971-; Vance, Courtney B.; Uggams, Leslie; Skloot, Rebecca, 1972- (HBO Home Video, 2017)
An African-American woman becomes an unwitting pioneer for medical breakthroughs when her cells are used to create the first immortal human cell line in the early 1950s.